1994
DOI: 10.1080/02701367.1994.10607624
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Optimal Scoring System with a Special Emphasis on Volleyball

Abstract: Scoring systems for two-team (two-person) net games are typically evaluated for accuracy, efficiency, and variability. This evaluation may be difficult if many points are involved, the probability of winning a point changes with service, and/or points are not scored every rally. A computer program that may be used to evaluate general scoring systems for accuracy, efficiency, variability, and expected score difference is presented. Four scoring systems, side-out, quick, side-out point, and bonus point, are anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
6
0
3
Order By: Relevance
“…The data confirm previous results that presented side-out and defense success as good performance indicators in volleyball (Fellingham et al, 1994;Palao, 2004Palao, , 2008. The values of success percentage found in side-out for college women are similar than values found at the women's international level (Japanese Volleyball Association, 1999;Palao, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The data confirm previous results that presented side-out and defense success as good performance indicators in volleyball (Fellingham et al, 1994;Palao, 2004Palao, , 2008. The values of success percentage found in side-out for college women are similar than values found at the women's international level (Japanese Volleyball Association, 1999;Palao, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…From a general perspective, there is an imbalance in success when teams are on side-out (team in reception) as compared to when teams are in serve and defense (serving team) (Palao, 2004;Silva, Lacerda, & Joao 2014). Researchers indicate that if a team has a side-out success of 70% in males and 63.5% in females, they will win the game (Fellingham, Collings, & McGown 1994;Palao, 2004Palao, , 2008. A closer analysis of success in side-out shows that it is composed of the opponent error in service, side-out success (first attack), counter-attack success (attack and block), and opponent errors.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on volleyball as a means of entertainment, the introduction of the rally-point Journal of Human Kinetics -volume 70/2019 http://www.johk.pl system has led to little variability in match duration and greater balance in scores, in both volleyball (Fellingham et al, 2009) and beach volleyball (Giatsis, 2003). To sign television agreements, little time variability is crucial (Fellingham et al, 1994;Giatsis, 2003). In addition, the International Volleyball Federation (FIVB) has introduced new GR changes in the game structure (the number of points played per sets and the number of sets played per match) at under-23 world championships in the last years (Stankovic et al, 2017), presumably to render volleyball more attractive to larger audiences.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the International Volleyball Federation (FIVB) has introduced new GR changes in the game structure (the number of points played per sets and the number of sets played per match) at under-23 world championships in the last years (Stankovic et al, 2017), presumably to render volleyball more attractive to larger audiences. Thus, effective GR features should be accurate and give the way to little variability in terms of minimum score differences between teams at the end of a game (Fellingham et al, 1994). However, no studies have been found on the impact of rule changes on team performance and coaching implications, or which may raise interest or increase uncertainty and excitement in an audience.…”
Section: Introductionmentioning
confidence: 99%
“…The rally is the basic unit of one point, the time when a team can score a point. It is differentiated from the other parts of the game, which are considered rest time (Fellingham, Collings, & McGown, 1994).…”
Section: Introductionmentioning
confidence: 99%